Outpatient Cryptococcal Antigen Screening Is Associated With Favorable Baseline Characteristics and Improved Survival in Persons With Cryptococcal Meningitis in Uganda. (21st July 2022) - Levin, Anna E; Bangdiwala, Ananta S; Nalintya, Elizabeth; Kagimu, Enock; Kasibante, John; Rutakingirwa, Morris K; Mpoza, Edward; Jjunju, Samuel; Nuwagira, Edwin; Naluyima, Rose; Kirumira, Paul; Hou, Cody; et al.
Abstract: Background: It is unknown whether persons with symptomatic cryptococcal meningitis detected during routine blood cryptococcal antigen (CrAg) screening have better survival than persons presenting with overt meningitis. Methods: We prospectively enrolled Ugandans with HIV and cryptocococcal meningitis from December 2018 to December 2021. Participants were treated with amphotericin-based combination therapy. We compared outcomes between persons who were CrAg screened then referred to hospital with those presenting directly to the hospital with symptomatic meningitis. Results: Among 489 participants with cryptococcal meningitis, 40% (194/489) received blood CrAg screening and were referred to hospital (median time to referral 2 days; interquartile range [IQR], 1–6). CrAg-screened persons referred to hospital had lower 14-day mortality than non–CrAg-screened persons who presented directly to hospital with symptomatic meningitis (12% vs 21%; hazard ratio, .51; 95% confidence interval, .32–.83; P = .006). Fewer CrAg-screened participants had altered mental status versus non–CrAg-screened participants (29% vs 41%; P = .03). CrAg-screened persons had lower quantitative cerebrospinal fluid (CSF) culture burden (median [IQR], 4570 [11–100 000] vs 26 900 [182–324 000] CFU/mL; P = .01) and lower CSF opening pressures (median [IQR], 190 [120–270] vs 225 [140–340] mmH2 O; P = .004) compared with non–CrAg-screened persons. Conclusions: Survival from cryptococcal meningitis was higher in persons with prior CrAg screening than those without CrAg screening. Altered mental status was the most potent predictor for mortality in a multivariate model. We suggest that CrAg screening detects cryptococcal meningitis at an earlier stage, as evidenced by a favorable baseline risk profile and notably fewer persons with altered mental status. Abstract : Persons with cryptococcal meningitis detected by blood cryptococcal antigen (CrAg) screening programs have characteristics of earlier disease and improved survival compared with persons presenting directly to hospital with symptomatic meningitis.